(untitled) (International Journal of Environmental Sciences, 2025)
A Novel Composite Papermaking Filler Was Developed By Combining Cellulose Microfibrils (Cmf) Derived From Melia Dubia, Ground Calcium Carbonate (Gcc), And Cationic Starch. This Study Utilised Cmf In Two Distinct Ways: As A Gcc–Cmf Composite Filler Added During Sheet Formation And As A Papermaking Additive Mixed With The Pulp Suspension. The Impacts Of These Approaches On Filler Flocculation, Retention, And Paper Properties Were Studied In Hardwood And Wheat Straw Pulps. Paper Sheets Filled With The Gcc–Cmf Composite Showed Markedly Higher Filler Retention ( 90%) Than Sheets With Conventional Gcc Alone. Sheets Containing The Composite Filler Also Exhibited Superior Tensile And Burst Indices Compared To Those With Standard Gcc Loading, Indicating Improved Strength At Equivalent Filler Contents. However, Using Cmf As A Direct Additive (Without Pre-Compositing With Gcc) Led To Somewhat Lower Enhancements In Strength And Retention. Composite Filler Sheets Became Denser As Filler Level Increased, Yet Maintained Optical Properties, Showing Slightly Higher Opacity And Comparable Brightness Relative To Conventional Filler Sheets. These Findings Demonstrate That Incorporating Melia Dubia Cmf In A Composite Filler Format Can Enable Higher Filler Usage In Paper Without Sacrificing And Even While Improving Overall Paper Strength And Quality.